2012
DOI: 10.1111/j.1740-0929.2012.01049.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary hesperidin supplementation on lamb performance and meat characteristics

Abstract: An experiment was conducted to examine the effects of supplementing feed with hesperidin or α-tocopheryl acetate on lambs' growth performance, carcass and meat characteristics. Sixteen male lambs were randomly assigned to four groups. One of the groups served as control and was given a basal diet, whereas the other three groups were given the same diet further supplemented with hesperidin at 1500 mg/kg, or hesperidin at 3000 mg/kg, or α-tocopheryl acetate at 200 mg/kg. At the end of the experiment, lambs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
2
14
0
4
Order By: Relevance
“…As shown in the present study, no significant effects of hesperidin or naringin dietary supplementation on feed intake, body weight and carcass traits of lambs were observed (Tables and ). Previous studies similarly demonstrated no effect of hesperidin (1.5 or 3 g kg −1 ) on feed intake, growth performance and carcass characteristics in lambs . No effect on feed intake was also observed after addition of alfalfa flavonoids (20, 60 or 100 mg kg −1 body weight) in the diet of dairy cows .…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…As shown in the present study, no significant effects of hesperidin or naringin dietary supplementation on feed intake, body weight and carcass traits of lambs were observed (Tables and ). Previous studies similarly demonstrated no effect of hesperidin (1.5 or 3 g kg −1 ) on feed intake, growth performance and carcass characteristics in lambs . No effect on feed intake was also observed after addition of alfalfa flavonoids (20, 60 or 100 mg kg −1 body weight) in the diet of dairy cows .…”
Section: Discussionmentioning
confidence: 70%
“…No significant effects of flavonoid dietary inclusion on meat quality characteristics such as pH, color, cooking loss and tenderness were found (Table ). Incorporation of hesperidin in lambs' diet at a level of 1.5 or 3 g kg −1 did not influence the values of pH and color parameters . No effects on meat pH and color were also recorded after incorporation of a citrus fruit extract rich in flavonoids (mainly naringin, quercetin and rutin; 150 mg kg −1 ) in the diet of lambs .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In further studies, supplementation of the lamb diet with 250-1000 mg α-tocopherol kg −1 feed extended the shelf life of meat kept under MAP by up to 4 days due to its reduction of lipid and haem pigment oxidation, although the resultant sensory traits were not assessed. Moreover, vitamin E was seen to have no effect on microbial inhibition on meat (Álvarez et al, 2008;Lauzurica et al, 2005;Ripoll et al, 2011) In recent years, several alternative dietary strategies based on plant phenolic antioxidants have been successfully checked for improving lamb meat preservation (Andrés et al, 2014(Andrés et al, , 2013Jerónimo et al, 2012;Luciano et al, 2009;Rivas-Cañedo et al, 2013;Simitzis, Ilias-Dimopoulos, Charismiadou, Biniari, & Deligeorgis, 2013;Simitzis et al, 2008), and, in particular, by using rosemary and/or its derivatives (Bañón et al, 2012;Morán, Rodríguez-Calleja, et al, 2012;Morán et al, 2013;Nieto, Díaz, Bañón, & Garrido, 2010;Ortuño, Serrano, Jordán, & Bañón, 2014;. Carnosic acid and, in particular, carnosol, the main active diterpenes in rosemary, can be deposited in lamb muscle at sufficient levels to have antimicrobial and antioxidant effects on meat (Jordán, Castillo, Bañón, Martínez-Conesa, & Sotomayor, 2014;Moñino, Martínez, Sotomayor, Lafuente, & Jordán, 2008).…”
Section: Introductionmentioning
confidence: 99%